The study of the reasons for delays in the implementation of construction projects in the Western Mountain region. (Sebha University Conference Proceedings, 2024)
The construction industry plays a vital role in developing infrastructure and enhancing the economies of countries. It includes projects such as roads, buildings, and health and educational institutions. To ensure the continuity and success of construction projects, this study was conducted to identify the reasons for delays in construction projects, pinpoint their main causes, and determine the reasons for stoppages and the potential consequences that may arise later on. A questionnaire was used as the research methodology, with 61 paper copies distributed to engineers and specialists in governmental institutions and private companies in the Western Mountain region. The questionnaires were collected and analyzed using statistical analysis software. The study found that owners, contractors, and consultants significantly contribute to delays due to several factors, including lack of experience, poor management, design changes, and delays in financial payments. Based on these results, the study proposed several recommendations, including attracting foreign investments, encouraging partnerships between contractors, enhancing educational programs in project management, and improving organizational mechanisms for contractors.